Energy saving and rapid establishment of granular microalgae system from tiny microalgae cells: Effect of decrease in upflow air velocity under intermittent aeration condition. (November 2022) - Wang, Qian; Yang, Yuyi; Shen, Qingyue; Chen, Xingyu; Li, Fengmin; Wang, Jixiang; Zhang, Zhenya; Lei, Zhongfang; Yuan, Tian; Shimizu, Kazuya
Graphical abstract: Highlights: Microalgae granulation was accelerated under intermittent aeration even at low UAV. MG completion was slightly delayed at low UAV with enhanced biomass accumulation. Energy input for MG completion of single-cell microalgae reduced 14.70% at low UAV. Microalgae mitigated the deterioration of nutrient performance at low UAV. LB- or TB-EPS proportion is critical for MG formation and maintenance. Abstract: The novel type of microalgae granules (MGs) derived from tiny microalgae cells has received extensive attention due to its great potential for nutrient remediation and resource recovery in wastewater treatment whereas the long start-up time with increased labor expenses remains a bottleneck. In this study, an operation strategy at reduced upflow air velocity (UAV = 0.49 cm/s in RA ) under intermittent aeration mode was proposed and compared with RB at a higher UAV (0.98 cm/s) in terms of MGs formation, maintenance, and energy consumption. Although the formation of MGs in RA was delayed for 12 days compared to RB, 40.78 % increase in chlorophyll- a content was detected in MGs in RA along with more cost-effective carbon, nitrogen, and phosphorus removals due to efficient microalgae assimilation and energy reduction. Results from this study provide new insight into minimizing energy input for rapid establishment and stable operation of MG systems towards environmentally sustainable wastewater management.